New Models of Emergency Prehospital Care That Avoid Unnecessary Conveyance to Emergency Department: Translation of Research Evidence into Practice? - Helen Anne Snooks; Mark Rhys Kingston; Rebecca Elizabeth Anthony; Ian Trevor Russell (The Scientific World Journal)
Background. Achieving knowledge translation in healthcare is growing in importance but methods to capture impact of research are not well developed. We present an attempt to capture impact of a programme of research in prehospital emergency care, aiming to inform the development of EMS models of care that avoid, when appropriate, conveyance of patients to hospital for immediate care. Methods. We describe the programme and its dissemination, present examples of its influence on policy and practice, internationally, and analyse routine UK statistics to determine whether conveyance practice has changed. Results. The programme comprises eight research studies, to a value of >£4 m. Findings have been disseminated through 18 published papers, cited 274 times in academic journals. We describe examples of how evidence has been put into practice, including new models of care in Canada and Australia. Routine statistics in England show that, alongside rising demand, conveyance rates have fallen from 90% to 58% over a 12-year period, 2,721 million fewer journeys, with publication of key studies 2003–2008. Comment. We have set out the rationale, key features, and impact on practice of a programme of publicly funded research. We describe evidence of knowledge translation, whilst recognising limitations in methods for capturing impact.